The Effect of Malignancy on Outcomes Following Revascularization for Critical Limb Ischemia: A Case–Control Study. (July 2018) - Calderbank, Tom; Karim, Ahmed; Wall, Mike; Syed, Arooj; Davies, Robert S. M.; Saratzis, Athanasios
Aim: Malignancy is common in patients presenting with critical lower limb ischemia (CLI). However, outcomes in patients with concomitant active malignancy and CLI have not been well defined in comparative prospective analyses. Using contemporary prospective data, we aimed to assess outcomes following revascularization in patients with CLI and active malignancy. Methods: A nested case–control study was performed using data from 2 tertiary referral centers for vascular disease. A total of 48 consecutive patients undergoing intervention for CLI who had a diagnosis of active malignancy were identified and matched to patients with CLI but no malignancy for age, sex, diabetes, and smoking. Patency rates and morbidity/mortality were assessed using duplex ultrasonography and regular clinical review. Results: A total of 48 consecutive patients (median age: 74.5 years; interquartile range: 68-80 years) with active malignancy and CLI were identified and case-matched (age, sex, diabetes, and smoking) to 48 patients undergoing intervention for CLI who had no malignancy. Major cardiovascular risk factors did not differ. All-cause mortality was 23% versus 12% ( P = .41) at 6 months and 54% versus 15% ( P < .001) at 12 months. None of the patients died due to complications relating directly to the lower limb intervention or within 30 days of the intervention. A total of 4 (8.3%) patients had required a major limb amputation at 6 months in both groups, compared with 5 (10.4%) patients with malignancy versus 4 (8.3%) patients without ( P = .73) at 12 months. Patency rates were similar at 12 months (73% vs 80%). Three patients had required reintervention in both groups (endovascular in all cases) at 12 months. Conclusion: Revascularization can be offered safely in selected patients with active malignancy; patency rates in those surviving to 1 year are similar to patients without malignancy.